2012
DOI: 10.1186/2008-2231-20-20
|View full text |Cite
|
Sign up to set email alerts
|

Report of methamphetamine use and cardiomyopathy in three patients

Abstract: BackgroundMethamphetamine (meth) is a stimulant used illegally around the world, including in Iran. Cardiomyopathy and cardiac failure may occur following chronic meth use and may cause the patients referred to the emergency department.Case reportsA 28-year old man and two women, ages 29 and 31-year-old, with a history of meth use, were admitted to the emergency department with severe dyspnea at rest. Each had sinus tachycardia with tachypnea and an echocardiogram that showed severe systolic dysfunction consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…They are consistent with results of several recent meta-analyses (OR=1.87; 95% CI=1.5–2.33) (Nikfar et al 2012b) and (OR=1.45; 95% CI=1.22–1.72) (Ross et al 2013) that found a modest elevation in risk of spontaneous miscarriage with antidepressant treatment. However, confounding as a result of unmeasured or incompletely measured health factors such as prior pregnancy loss, obesity, substance abuse, etc, may confound the findings.…”
Section: Spontaneous Abortionsupporting
confidence: 92%
“…They are consistent with results of several recent meta-analyses (OR=1.87; 95% CI=1.5–2.33) (Nikfar et al 2012b) and (OR=1.45; 95% CI=1.22–1.72) (Ross et al 2013) that found a modest elevation in risk of spontaneous miscarriage with antidepressant treatment. However, confounding as a result of unmeasured or incompletely measured health factors such as prior pregnancy loss, obesity, substance abuse, etc, may confound the findings.…”
Section: Spontaneous Abortionsupporting
confidence: 92%
“…3. Methamphetamine (crystal meth): as for cocaine and amphetamines above, there are reports of cardiomyopathy [73], hypertension, aortic dissection, acute coronary syndromes, pulmonary arterial hypertension and methamphetamine-associated cardiomyopathy [74] and in rat models cardiac pathology [75]. Recommendations as for Cocaine and Ecstasy above.…”
Section: Heartmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 In particular, METH has been associated with a myriad of adverse effects on the circulatory system, including cardiomyopathy, hypertension, arrhythmia, myocardial ischemia, acute coronary syndrome, cardiac failure and sudden death. 6 , 7 , 8 In METH abusers with acute aortic dissection or coronary syndrome, vascular structural alterations have been found in the myocardium in a number of clinical cases, indicating that METH can cause toxic effects on the blood vessels. 9 , 10 The above studies suggest that vascular endothelial cells may be a key target in METH-caused cardiovascular pathophysiologic alterations.…”
mentioning
confidence: 99%